Transcatheter Mitral Valve Replacement: Procedural Planning, Utility, and Applicability. Issue 2 (15th September 2020) - Alexis, Sophia L.; Sengupta, Aditya; Zaid, Syed; Kaple, Ryan; Ahmad, Hasan; Malik, Aaqib; Biswas, Medha; Tang, Gilbert H. L.
Abstract : Since the first native transcatheter mitral valve implantation in 2012, transcatheter mitral valve replacement (TMVR) has expanded its use to degenerated bioprostheses, failed annuloplasty ring repair, and mitral annular calcification. However, high-screen failure rates in trials have persisted due to predicted left ventricular outflow tract obstruction and unfavorable anatomy. Preprocedural planning in this patient population with multidetector computed tomography and transesophageal echocardiography is paramount to intraprocedural success. In patients with favorable left ventricular outflow tract anatomy who are not surgical candidates, the transseptal approach is preferred. In those who are surgical candidates, TMVR can be performed via a transapical or transatrial approach. Currently, a plethora of TMVR devices targeting the native mitral pathologies are undergoing clinical trials. Data have consistently shown the greatest benefit of this procedure in native mitral regurgitation and failed bioprostheses rather than failed annuloplasty rings or mitral annular calcification. With technological advancement and careful patient selection, this therapy will serve as a complement to surgical and TMV repair and will continue to expand to address MV diseases in a broader patient population.